Hierarchical MnOx/ZSM-5 as Heterogeneous Catalysts in Conversion of Delignified Rice Husk to Levulinic Acid - Yuni Krisyuningsih Krisnandi; Dita Arifa Nurani; Anastasia Agnes; Ralentri Pertiwi; Noer Fadlina Antra; Alika Rizki Anggraeni; Anya Prilla Azaria; Russell Francis Howe (Universitas Gadjah Mada, 2019)
Hierarchical ZSM-5 zeolite was synthesized using a double template method using TPAOH and PDDA as templates, while microporous ZSM-5 was also prepared using only TPAOH as a template. The syntheses then were followed by impregnation with Mn(II) c.a. 2 wt.% and calcination at 550 °C to obtain MnOx/ZSM-5 zeolite catalysts. Extensive characterization of the zeolite catalysts was performed using XRD, SEM, AAS, EDX, FTIR and BET measurement. The characterization showed that hierarchical or mainly mesoporous ZSM-5 was successfully synthesized, having added features compared to the microporous counterpart. The catalysts then were used in conversion reaction of delignified rice husk to levulinic acid, a platform chemical. As a comparison, a certain amount of MnCl2.4H2O was used as a homogeneous catalyst in a similar reaction. The product of the reaction was separated and analyzed with HPLC. It showed that 8 h was the optimum condition for the conversion, with hierarchical MnOx/hi_ZSM-5 catalyst gave the highest amount of levulinic acid (%Y of 15.83%), followed by microporous MnOx/mi_ZSM-5 (%Y of 10%). The % yield of levulinic acid using homogeneous Mn(II) catalyst (%Y of 8.86%) gave more charcoal as a product. Meanwhile, the stability of the zeolite catalysts after the reaction has also been investigated, mainly by analyzing the FTIR spectra and EDX data of the used catalysts after separated and calcined at 550 °C. From the analysis, some of the silica and alumina are leached from the framework, as well as the manganese oxide due to acidic condition at the beginning of the reaction. Nevertheless, it can be concluded that the conversion took place as the interaction between the cellulose and either MnOx in zeolites or Mn2+ ions in the solution, with the support of porous ZSM-5 framework. Hierarchical system somehow assists the ZSM-5 structure stays intact.